2019
DOI: 10.1155/2019/7202731
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Combined Central Retinal Artery and Vein Occlusion

Abstract: Purpose To describe the clinical features of combined central retinal artery and vein occlusion (CCRAVO). Methods This retrospective study included 33 admitted patients (33 eyes) who had CCRAVO. Clinical data, such as age, gender, best-corrected visual acuity (BCVA), intraocular pressure (IOP), findings on fundus color photography and fundus fluorescein angiography (FFA), and information about follow-up, were collected and analyzed. Results The age of the patients with CCRAVO ranged from 22 to 78 years, with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
(31 reference statements)
1
6
0
Order By: Relevance
“…Prior studies on CRAO secondary to CRVO have reported that the incidence of neovascularization ranges widely, from 0 to 81%. 10 , 11 In our study, all three (100%) of the patients with CRAO caused by CRVO developed NVA and NVG.…”
Section: Discussionsupporting
confidence: 50%
“…Prior studies on CRAO secondary to CRVO have reported that the incidence of neovascularization ranges widely, from 0 to 81%. 10 , 11 In our study, all three (100%) of the patients with CRAO caused by CRVO developed NVA and NVG.…”
Section: Discussionsupporting
confidence: 50%
“…The exact mechanism of combined occlusions is not known. It is presumed that central retinal vein occlusion (CRVO) leads to increase in intraluminal pressure of the retinal capillary bed, which is then transmitted to the retinal artery to decrease its blood flow 14. In our case, a long-standing CRVO led to a subsequent central retinal artery occlusion.…”
Section: Discussionmentioning
confidence: 77%
“…In the future, electroretinography can also be used to further analyze the relationship between retinal and optic nerve function and explore the prognosis of CRVO in young patients. Although the prognosis of CRVO in young patients is generally favorable, studies have reported that patients with combined central retinal artery and vein occlusion may be younger than the patients who had only CRVO or CRAO [71,72]. In a previous study, mean age of the patients with combined central retinal artery and vein occlusion was 48.8 ± 14.1 years [72].…”
Section: Differences In Prognosismentioning
confidence: 92%
“…Although the prognosis of CRVO in young patients is generally favorable, studies have reported that patients with combined central retinal artery and vein occlusion may be younger than the patients who had only CRVO or CRAO [71,72]. In a previous study, mean age of the patients with combined central retinal artery and vein occlusion was 48.8 ± 14.1 years [72]. In these patients, artery occlusion could be secondary to CRVO, which increases the intraluminal pressure of the retinal capillary bed, and the pressure is transmitted to the retinal artery to decrease or even stop the blood flow.…”
Section: Differences In Prognosismentioning
confidence: 99%